Characterization of antibiosis to diabrotica speciosa (Coleoptera: Chrysomelidae) in Brazilian Maize Landraces - Costa, Eduardo Neves [UNESP]; Nogueira, Luciano [UNESP]; De Souza, Bruno Henrique Sardinha; Ribeiro, Zulene Antônio [UNESP]; Louvandini, Helder; Zukoff, Sarah Natalie; Júnior, Arlindo Leal Boiça [UNESP] (Oxford University Press (OUP), 2018)
Resistance to insect pests can be found in several native, landrace plants and can be an important alternative to conventional control methods. Diabrotica speciosa (Germar) (Coleoptera: Chrysomelidae) larvae are important maize (Zea mays L.) (Cyperales: Poaceae) root pests and finding native resistance in landraces would greatly contribute to maize-breeding programs aimed at controlling this pest. This study investigated whether the growth, survival, oviposition rhythm, fecundity, and fertility of D. speciosa are negatively influenced by specific maize landraces, and the existence of any morphological barriers in the roots that may correlate with plant resistance to the larval attack. Nineteen genotypes (17 landraces and 2 cultivars) were screened for antibiosis in assays that were conducted in the laboratory using seedling maize plants where the development time, longevity, weight, total survival, and sex ratio of adults were evaluated. Out of nineteen genotypes, eight were selected according to their resistance levels for an additional rearing study evaluating oviposition and fecundity. Landrace Pérola and cultivar SCS 154-Fortuna were classified as resistant because they increased the maturation period from larva to adult and decreased survivorship; and the landrace Palha Roxa was also classified as resistant for showing a lower fertility rate than other landraces. Resistant landraces that were infested by D. speciosa larvae showed greater amounts of some morphological barriers comparing with uninfested plants. The landraces classified as resistant may be considered in future plant-breeding programs, aiming to develop resistant maize cultivars to D. speciosa larval attack.
Keywords: Integrated pest management; Native resistance; Rootworm; Soil pest; Zea mays